2020
DOI: 10.2147/cmar.s262314
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge of Cervical Cancer and Associated Factors Among Women Attending Public Health Facilities in Eastern Ethiopia</p>

Abstract: This study was done to assess women's knowledge of cervical cancer and associated factors. Materials and Methods: We conducted a facility-based cross-sectional study in eastern Ethiopia from January 1 to May 30, 2019. A convenient sampling technique was used to include 1181 women in this study. Information on socio-demographic characteristics, sexual history, knowledge and awareness of women was collected using face-to-face interview. The data were cleaned, coded and entered into EPI-info version 3.5.4 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Seven diverse viruses have been connected to the growth of different types of human cancer, such as human papillomavirus, Epstein-Barr virus, human T-cell lymphotropic virus, hepatitis B virus, hepatitis C virus, Merkel cell polyomavirus and Kaposi's sarcoma herpes virus. Although infection of human papilloma virus (HPV) is considered one of the most essential factor for the growth of cervical cancer [19] but various other factors also connected for the development of cervical cancer which include infection of C. trachomatis, early age at first coitus, premarital sexual and extramarital sexual activity, early age pregnancy, multiple sexual partners of the male and females, husbands, and uncircumcised sexual partners [20,21]. Though, the infection of HPV is generally transient but little percentage of females showed persistent infection which has connected with the development of cervical cancer.…”
Section: Role Of Infections In the Etiology Of Cervical Cancermentioning
confidence: 99%
“…Seven diverse viruses have been connected to the growth of different types of human cancer, such as human papillomavirus, Epstein-Barr virus, human T-cell lymphotropic virus, hepatitis B virus, hepatitis C virus, Merkel cell polyomavirus and Kaposi's sarcoma herpes virus. Although infection of human papilloma virus (HPV) is considered one of the most essential factor for the growth of cervical cancer [19] but various other factors also connected for the development of cervical cancer which include infection of C. trachomatis, early age at first coitus, premarital sexual and extramarital sexual activity, early age pregnancy, multiple sexual partners of the male and females, husbands, and uncircumcised sexual partners [20,21]. Though, the infection of HPV is generally transient but little percentage of females showed persistent infection which has connected with the development of cervical cancer.…”
Section: Role Of Infections In the Etiology Of Cervical Cancermentioning
confidence: 99%
“…Only 12.9% had base-level knowledge about vaginal bleeding after coitus could be a sign of cervical cancer, which is low compared to a study in India, 27%, 41 very low compared to different studies reported. 38,40 The baseline knowledge levels on vaginal bleeding between periods and foul-smelling vaginal discharge as a symptom of cervical cancer were lower than studies reported. 38,41 After menopause, vaginal bleeding may be an indication of cervical cancer.…”
Section: Discussionmentioning
confidence: 84%
“…This score is lower than a study done in Eastern Ethiopia, 24.2%. 40 At the base level, 25.7% of study participants knew that multiple sex partners could be a risk factor, which is higher than a study of 6%. 41 This difference in awareness could be due to awareness of HIV education received as a part of the curriculum.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations